When Magnus Johanson turned fifty: Materiality, place-making and early-twentieth-century Swedish Baptist birthday parties - Holmes, Janice (Approaching Religion, 2023)
This article examines birthday party decorations as a way of understanding the materiality and religious place-making of an expanding Baptist congregation in central Sweden in the early twentieth century. The fiftieth birthday party for Magnus Johanson, held at Salem Chapel in Falun, Dalarna county, in 1906, was decorated with birch branches, large Swedish flags and bunting and an elaborately laid table featuring coffee cups and refreshments. From an analysis of these material elements and a deeper investigation into the lives of Johanson and his wife Kristina, it can be seen that evangelicals had a flexible approach to their ‘sacred’ spaces. Social activities and the act of decorating them created not only a sense of congregational fellowship and belonging but also the opportunity for congregations to display their connection to external cultural and political identities. Through the construction of chapel buildings and their subsequent decoration, male and female members were able to demonstrate a complementary creativity. Together they contributed to the cre-ation of Salem as a multi-purpose, comfortable and accepted place within Falun’s evolving religious landscape.